The Use of Vegetable Waste Silage Supplemented with Mineral and Alginate as Feeding for Sheep - A. Muktiani; J. Achmadi; B.I. M. Tampoebolon; R. Setyorini (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The aim of the experiment was to find the most appropriate supplement for sheep fed on vegetable waste silage–based diet to produce better weight gain. Sixteen male local sheep (average body weight of 13.27+2.82 kg ) were randomly divided into four groups according to completely randomised design. Each group received one of four treatments i.e. T0 (50% field grass + 50% concentrate), T1 (50% silage of vegetable waste + 50% concentrate), T2 (T1 diet + mineral Zn 20 ppm, Cr 2 ppm), and T3 ( T2 diet + 1% alginate). After two weeks of preliminary period, sheep were subjected to 12 weeks of observation. In general, the vegetable waste silage based diet (T1,T2, T3) resulted in better crude protein (CP) intake and weight gain than the T0 diet. Each treatment of T0, T1, T2, and T3 resulted in Protein consumption of 36,48 ; 45,81 ; 53,59 ; 40,75 g, and weight gain of 75; 105; 121; 109 g/day, respectively. Mineral supplementation (T2) resulted in higher rates of weight gain and feed efficiency compared to the mixed mineral and alginate supplementation (T3), therefore leading to the conclusion that only Zn and Cr mineral supplementation is needed for the vegetable waste silage used as sheep ruminant feed.